Les engagements infrapolitiques des jeunes en difficulté d’insertion : entre institutions et pratiques autonomes - Fabrice Plomb; Caroline Henchoz (Sociétés et Jeunesses en Difficulté)
In social research, the question of youth commitment is used to being construed through young people’s political involvement, or with reference to it. The analysis of interviews and a long-term participant observation of precarious young people between 15 and 30 years old demonstrate other types of commitment that pertain to what John C. Scott (2009) names infrapolitics. These commitment types don’t aim at any kind of exemption from supervision or dependency (such as self-determination usually dealt with in political studies). They refer to the discreet or hidden resistance of these youth to the constraints of salaried employment formulated by the social institutions in charge. In order to be heard, these young people developed veritable clandestine strategies of resistance involving themselves relationally so that their viewpoint, contrary to institutional expectations, was acknowledged and accepted by the representatives of said institutions. We conclude by showing the skills these youth harnessed and how they were able to gain autonomy by working toward commitment.